PENGARUH UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2013 – 2015) - Tulus Prijanto, Andri Veno & Chuzaimah (Universitas Slamet Riyadi, 2017)
This research has point of view to analysied size of company influence, andliquidity about performance of the company. The sample among 62 manufacturecompany in Indonesian stock exchange (BEI) in 2013 – 2015 period. Sampling tehnikusing one time method, covers from variable and data processing with regretionlogistic multiple analysis. Liquidity variable and company size became independentvariable, proxited with current ratio for company size and liquidity. Currentlydependent variable of company performance are proxited with ROA (return of asset).This analysts using double linear regrestion, and the result of double regrestionanalysts represent between liquidity and size positively and significantly influence ofcompany performance.Keyword: liquidity, size of company, performance of the company, cross sectional